2017
DOI: 10.3390/brainsci7080100
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Dysfunction after Mild Traumatic Brain Injury

Abstract: A mild traumatic brain injury (mTBI) is a complex pathophysiologic process that has a systemic effect on the body aside from solely an impairment in cognitive function. Dysfunction of the autonomic nervous system (ANS) has been found to induce abnormalities in organ systems throughout the body, and may contribute to cardiovascular dysregulation and increased mortality. Autonomic dysfunction, also known as dysautonomia, has been studied in moderate and severe TBI, and has emerged as a major contributing factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
100
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(111 citation statements)
references
References 35 publications
2
100
0
3
Order By: Relevance
“…Although not specifically studies of PTH, prior studies have identified symptoms of dysautonomia among those with TBI . Studies of autonomic dysfunction following mTBI have assessed heart rate variability, pupillary light reflex, arterial pulse wave, and graded exercise testing .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although not specifically studies of PTH, prior studies have identified symptoms of dysautonomia among those with TBI . Studies of autonomic dysfunction following mTBI have assessed heart rate variability, pupillary light reflex, arterial pulse wave, and graded exercise testing .…”
Section: Discussionmentioning
confidence: 99%
“…Although not specifically studies of PTH, prior studies have identified symptoms of dysautonomia among those with TBI. 22,28,46 Studies of autonomic dysfunction following mTBI have assessed heart rate variability, 19 pupillary light reflex, arterial pulse wave, and graded exercise testing. 26,27,35 One such study showed head-upright tilt table abnormalities similar to postural orthostatic tachycardia syndrome (POTS) in youth with persistent post-concussion syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a primary example, the association between pathologic central nervous system processes as a consequence of repetitive head trauma and cardiovascular pathology is a compelling but speculative realm in need of testing. To date, among ASF athletes, the acute and long‐term effects of postconcussive autonomic dysregulation80 and sympathetic nervous system overstimulation on cardiovascular parameters have not been explored. A second intriguing unknown worthy of study is the impact of NSAID use on both cardiovascular and renal physiology.…”
Section: Future Directionsmentioning
confidence: 99%